El prisma de la desigualdad mundial: una clasificación multidimensional de países - Rogelio Madrueño; Sergio Tezanos (Revista Internacional de Cooperación y Desarrollo)
This paper provides a broad overview of the issue of rising inequality and builds an international and multidimensional taxonomy of economic inequality. We use a hierarchical cluster analysis that enables us to identify five groups of countries with distinctive economic inequality characteristics, which show that, despite national and regional specificities, both developed and developing countries face important difficulties in reducing social and economic disparities. The resulting classification may be useful to map out the various national realities of economic inequality across countries. The results suggest that there should be avoided a “one size fits all” international strategy to address the different patterns of inequality that we have identified across the World. Still, it is crucial to acknowledge the importance of the particularities of each cluster and each geographic region regarding a complex and multidimensional phenomenon that has become a global challenge for the 21st Century